Christmas with Anne : and other holiday stories - Montgomery, L. M. (Lucy Maud), 1874-1942 (Bantam, 2001)
A collection of Christmas and New Year's tales in addition to chapters about Christmas taken from the Anne books, all of which present the spirit of giving.